Erythropoietin in patients with traumatic brain injury and extracranial injury—A post hoc analysis of the erythropoietin traumatic brain injury trial. Issue 3 (September 2017) - Skrifvars, Markus B.; Bailey, Michael; French, Craig; Presneill, Jeffrey; Nichol, Alistair; Little, Lorraine; Duranteau, Jacques; Huet, Olivier; Haddad, Samir; Arabi, Yaseen; McArthur, Colin; Cooper, D. James; et al.
Abstract : BACKGROUND: Erythropoietin (EPO) may reduce mortality after traumatic brain injury (TBI). Secondary brain injury is exacerbated by multiple trauma, and possibly modifiable by EPO. We hypothesized that EPO decreases mortality more in TBI patients with multiple trauma, than in patients with TBI alone. METHODS: A post hoc analysis of the EPO-TBI randomized controlled trial conducted in 2009 to 2014. To evaluate the impact of injuries outside the brain, we calculated an extracranial Injury Severity Score (ISS) that included the same components of the ISS, excluding head and face components. We defined multiple trauma as two injured body regions with an Abbreviated Injury Scale (AIS) score of 3 or higher. Cox regression analyses, allowing for potential differential responses per the presence or absence of extracranial injury defined by these injury scores, were used to assess the effect of EPO on time to mortality. RESULTS: Of 603 included patients, the median extracranial ISS was 6 (interquartile range, 1–13) and 258 (43%) had an AIS score of 3 or higher in at least two body regions. On Cox regression, EPO was associated with decreased mortality in patients with greater extracranial ISS (interaction p = 0.048) and weakly associated with differential mortality with multiple trauma (AIS score > 3 or in two regions, interaction p = 0.17). At 6 months in patients with extracranial ISS higher than 6, 10 (6.8%) of 147 EPO-treated patients compared with 26 (17%) of 154 placebo-treated patients died (risk reduction, 10%; 95% confidence interval, 2.9–17%; p = 0.007). CONCLUSION: In this post hoc analysis, EPO administration was associated with a potential differential improvement in 6-month mortality in TBI patients with more severe extracranial injury. These findings need confirmation in future clinical and experimental studies. LEVEL OF EVIDENCE: Therapeutic study, level III. Abstract : Supplemental digital content is available in the text.